Activation of nucleus accumbens projections to the ventral tegmental area alters molecular signaling and neurotransmission in the reward system - Khayat, Alaa; Yaka, Rami (Frontiers in Molecular Neuroscience, 2024)
The nucleus accumbens (NAc) and the ventral tegmental area (VTA) are integral brain regions involved in reward processing and motivation, including responses to drugs of abuse. Previously, we have demonstrated that activation of NAc-VTA afferents during the acquisition of cocaine conditioned place preference (CPP) reduces the rewarding properties of cocaine and diminished the activity of VTA dopamine neurons. In the current study, we examined the impact of enhancing these inhibitory inputs on molecular changes and neurotransmission associated with cocaine exposure. Our results unveiled significant reductions in extracellular signal-regulated kinase (ERK) levels in the VTA and medial prefrontal cortex (mPFC) of both cocaine-treated groups compared with the saline control group. Furthermore, optic stimulation of NAc-VTA inputs during cocaine exposure decreased the expression of GluA1 subunit of AMPA receptor in the VTA and mPFC. Notably, in the NAc, cocaine exposure paired with optic stimulation increased ERK levels and reduced GluA1 phosphorylation at Ser845 as compared with all other groups. Additionally, both cocaine-treated groups exhibited decreased levels of GluA1 phosphorylation at Ser831 in the NAc compared with the saline control group. Moreover, cocaine exposure led to reduced ERK, GluA1, and GluA1 phosphorylation at Ser845 and Ser831 in the mPFC. Augmentation of GABAergic tone from the NAc during cocaine conditioning mitigated changes in GluA1 phosphorylation at Ser845 in the mPFC but reduced ERK, GluA1, and GluA1 phosphorylation at Ser831 compared with the saline control group. Interestingly, enhancing GABAergic tone during saline conditioning decreased GluA1 phosphorylation at Ser831 compared with the saline control group in the mPFC. Our findings highlight the influence of modulating inhibitory inputs from the NAc to the VTA on molecular signaling and glutamatergic neurotransmission in cocaine-exposed animals. Activation of these inhibitory inputs during cocaine conditioning induced alterations in key signaling molecules and AMPA receptor, providing valuable insights into the neurobiological mechanisms underlying cocaine reward and cocaine use disorder. Further exploration of these pathways may offer potential therapeutic targets for the treatment of substance use disorder.